Occurrence, Impact, and Management of Rare Earth Elements in Vegetables and Soil: A Detailed Review of Asian Perspectives - Mithilesh Kumari Gupta; Neetu Singh; Anju Jha; Saroj Sharma (The Bioscan, 2024)
Rare earth elements (REEs), comprising 17 elements with unique magnetic and catalytic properties, are increasingly important in technological applications. However, their accumulation in soil and vegetables poses environmental and health risks. This review provides an in-depth analysis of the distribution, sources, and impacts of REEs in soil and vegetables across Asia. It examines the challenges associated with REE contamination, highlights current monitoring and management practices, and discusses future research directions.